Vocatives in the Balkans - Hill, Virginia (Revista Letras, 2017)
This paper argues that: (i) vocative nouns project beyond DP, to a VocP level that maps the basic pragmatic features involved in the derivation of nominal expressions conveying a direct address; (ii) this pattern can be generalized cross-linguistically; (iii) variations within this pattern are predictable in a principled way, and one particular example arises in the case of reverse vocatives; (iv) reverse vocatives are areally restricted in a way that indicates a particular language contact situation.